Human displacement and ecological sustainability in Africa: evidence from FBARDL and Fourier-based causality analysis - Bildirici, Melike E. (TAYLOR & FRANCIS INC, 2026)
Forced displacement has become an increasingly pressing global challenge, particularly in Africa where refugee movements interact with fragile development structures and growing environmental pressures. Despite the rapid rise in refugee flows across the continent, the literature largely examined refugee dynamics in the context of humanitarian, social and economic perspectives by leaving the relationship between refugee movements, ecological footprint and sustainable development largely unexplored. To fill this gap, the paper empirically investigated the long-run relationship and Granger causality among refugees population, ecological footprint, sustainable development and economic growth in Uganda, Kenya, Congo, and the Democratic Republic of Congo over the period 1990-2023 by the Fourier-based Autoregressive Distributed Lag and the Fourier-based Granger causality test. Before model-based policy recommendations, the robustness of the results is thoroughly evaluated through ARDL methods, residual diagnostics (Jarque-Bera and kurtosis tests), lag-variant Granger causality tests, Fourier F-tests and forecast performance evaluations. The results revealed the existence of cointegration among the variables. Granger causality results indicated a unidirectional causality running from refugee movements to both ecological footprint and sustainable development, and economic growth, and unidirectional causality from EF to SDI except Uganda. Overall, the results demonstrated that refugee movements significantly influence both ecological footprint and sustainable development in the selected countries by suggesting that refugee policies should be integrated with environmental management and sustainable development strategies rather than addressed solely within a humanitarian framework.
Keywords: Refugee population; sustainable development; ecological footprint; FBARDL; Fourier causality; ENVIRONMENTAL-CHANGE; ENERGY-CONSUMPTION; SULFUR-DIOXIDE; REFUGEES; IMPACT; TECHNOLOGIES; POPULATION; RESOURCES; FOOTPRINT; Science & Technology - Other Topics; Environmental Sciences & Ecology